Dissecting Between-Plant and Within-Plant Wage Dispersion - Evidence from Germany - Daniel Baumgarten; Gabriel Felbermayr; Sybille Lehwald (Center for Economic Studies and ifo Institute (CESifo), 2018)
Using rich linked employer-employee data for (West) Germany between 1996 and 2014, we analyze the most important drivers of the recent rise in German wage dispersion and pin down the relative contribution of plant and worker characteristics. Moreover, we separately investigate the drivers of between-plant and within-plant wage dispersion. We also analyze the sources of the recent slowdown in German wage inequality and compare the results for West Germany to the ones for East Germany. We disentangle the relative contribution of each single variable to the rise in wage dispersion using recentered influence function (RIF) regressions. The most important drivers of wage dispersion are industry effects and the bargaining regime. The former predominantly works through the wage structure effect while, in the latter case, both the decline in collective bargaining coverage and the strong increase in wage dispersion within the group of covered plants have played a substantial role. While education has been another factor contributing to both between-plant and within-plant wage inequality, other candidate factors such as plant size, the exporting status, plant technology, and investment intensity are all of little if any direct quantitative importance for the increase in wage dispersion.
Keywords: J31; J51; C21; F16; 330; wage inequality; decomposition; RIF-regression; linked employer-employee data